The palaeobiology of the late Permian dicynodont Endothiodon (Therapsida, Anomodontia) - Maharaj, Iyra Esmen Maeve (Department of Biological Sciences, 2023)
Among the dicynodonts, the late Permian genus Endothiodon is unique for its cranial morphology and unusual dentition. Despite the extensive amount of Endothiodon cranial material recovered from Gondwanan deposits worldwide, there is much that is unknown about its palaeobiology. This thesis provides fresh insights into the taxonomy, dental histology and postural reconstructions of Endothiodon based on the crania and postcrania of the taxon. Despite a few interventions over the years, the taxonomy of the genus Endothiodon has been in a stateof confusion since the late 19th century. While an abundance of cranial material from various Gondwanan deposits has added insights into intrageneric variation, a formal taxonomic review of the genus and species therein has never been conducted and thus remains unresolved. A sample of 131 Endothiodon skull specimens were examined to assess anatomical variation,and 24 taxonomically relevant characters were determined and scored in a phylogenetic analysis. The results suggest that only three Endothiodon species are valid: E. bathystoma, E. mahalanobisi, and E. tolani. The presence of E. mahalanobisi is evidenced in east Africa as well as India for the first time. In combination with micro-computed tomographic (µ-CT) scanning, a new approach of transversely sectioning each jaw at multiple levels of depth was employed, allowing the dental and alveolar bone microstructureto be described at varying depths in the jaw. The results show that South African E. bathystoma had a soft tissue attachment, and its tooth eruption sequence agrees with the Zahnreihen mode of tooth replacement, where teeth drift from the lingual margin labially, where they are eventually resorbed. This investigation also shows histologically that the teeth from the single-rowed maxillae are replaced less frequently than that of multi-rowed dentaries. Although some postcrania of Endothiodon have been recovered in recent years from the Karoo Basin ofSouth Africa and from the K5 Formation of Mozambique, to date no studies of the functional morphology of the postcranial skeleton have been conducted. Three-dimensional models of forelimb and hindlimb elements were used in digital articulation, showing that mobility in the forelimb was more restricted than that of the hindlimb. The results also show that the stationary posture of Endothiodon follows that of other dicynodonts, whereby the hindlimb is held higher off the ground than the forelimb. Overall, this thesis has unravelled the taxonomy of Endothiodon, provided novel information regarding its complex dental histology and tooth replacement patterns in both the maxillae and dentaries, and has permitted a concise assessment of its posture.